Multi-site Cr3+ occupation-related broadband NIR luminescence in Cr3+-doped Li3Mg2NbO6. Issue 33 (6th August 2021) - Xiao, Fen; Xie, Chengning; Xie, Shikun; Yi, Rongxi; Yuan, Huiling; Zhou, Haolin
Abstract : Broadband NIR luminescence from the Li3 Mg2 NbO6 :Cr 3+ phosphor is related to the multi-site occupation behavior of Cr 3+ . Abstract : Broadband near-infrared (NIR) luminescent materials have recently attracted significant attention as advanced smart optical sources for NIR spectroscopy. In this work, a broadband NIR emission from 650 nm to 950 nm with a full width at half maximum up to 160 nm was acquired in a Cr 3+ -activated Li3 Mg2 NbO6 phosphor under blue excitation. Based on the structural simulation and spectral characteristic analysis, this broad spectrum is inferred to be composed of emissions from Cr 3+ substituting three different crystallographic sites with different crystal field environments. The temperature-dependent luminescence properties of Li3 Mg2 NbO6 :Cr 3+ were revealed to be multiple thermal processes related to the multi-site occupation behaviors of Cr 3+ ions in the host. A 10 mW NIR output was achieved from the phosphor-converted LEDs fabricated by the as-prepared Li3 Mg2 NbO6 :Cr 3+ phosphor and blue InGaN chip. The obtained results have offered significant insight into exploring novel transition metal ion-based broadband NIR materials for phosphor-converted LEDs.